The commitment of organizational justice: A case study - Putu Irma Yunita; Komang Keika Yanti Darma (Universitas Pendidikan Nasional, 2020)
This research was conducted at the ISTA Cooperative Penatih Denpasar. ISTA Cooperative Penatih Denpasar, in efforts to foster human resources especially those related to employee commitment to the organization, always strove to provide justice to employees, which was distributive justice, procedural justice, and interactional justice. But the reality that occurred at the ISTA Cooperative Penatih Denpasar was not all employees have a high commitment. Commitments among employees appeared to be declining, an indication of declining employee commitment can be illustrated by a note from the personnel department that some of the employees were late coming to work, skipping, left office during working hours and there were even some employees who submitted resignation. This study aimed to examine the Commitment to Organizational Justice (Case Study at ISTA Cooperative Penatih Denpasar). The population of this study was all employees at ISTA Cooperative Penatih Denpasar with 33 respondents. The type of data used in this research was quantitative data and the data collection technique used was a documentation study and questionnaire. The data analysis technique used in this study were classical assumption test, multiple linear regression analysis, and model feasibility test. The result of this research showed that; 1) Distributive justice has a positive and significant effect on commitment. 2) Procedural justice has a positive and significant effect on commitment. 3) Interactional justice has a positive and significant effect on commitment. 4) Distributive justice, procedural justice, and interactional justice have a positive and significant effect on commitment.